Medicinal Importance of Pleurotus species (Oyster Mushroom): A review - Haseeb Irfan; Amna Saleem; Maham gill; Ayesha Ali; Momina Akmal (CV. Multi Kreasi Media, 2022)
Pleurotus ostreatus is a Macro- Fungi. It belongs to the class Basidiomycota and the family Agaricaceae. It is the second-largest cultivated edible mushroom for various purposes like food and medicine. Somehow cardiometabolic parameters and various diseases like cancer can be treated with the intake of mushrooms through diet. In the modern world, oyster mushrooms are known for their high-quality protein, fiber, vitamins, and many other healing properties. It is used as a health enhancer, more than any other mushroom. Many biologically active compounds in this mushroom include polysaccharides, lipopolysaccharides, proteins, peptides, glycoproteins, nucleosides, triterpenoids, lectins, lipids, and their derivatives. In this review, an extensive database search and analysis was performed to change the status and to predict the biomedical potential of the Oyster mushroom (Pleurotus). (Sarma, Saha et al. 2018)